Integration of transcriptome and mendelian randomization elucidates the protective role of aspirin in pulmonary tuberculosis development - Wei Tan; Li Zhang; Shanmei Wang; Yu Chen; Hanqing Yu; Xinmiao Song; Changwei Wu; Ping Jiang; Shuo Liang (Functional & Integrative Genomics, 2026)

Seismic performance evaluation of bridge isolated by damping enhanced-friction pendulum system considering variable friction effect - Wenzhi Zheng; Zhongkai Yi; Wanchen Meng; Ping Tan; Jian Li; Xijun Ye; Yanhui Liu (Soil Dynamics and Earthquake Engineering, 2026)

Mechanistic insights into Cu impurity retention and its effective removal in direct recycling of lithium-ion batteries - Wenlin Yan; Wei Li; Qiushi Miao; Mengchen Liu; Ershuang Lu; Jiao Lin; Minji Lee; Haichen Lin; Shuangjie Tan; Varun Gupta; Zheng Chen; Ping Liu (Chemical Engineering Journal, 2026)

Reactive oxygen species–mediated enhancement of cadmium phytoextraction in ramie (Boehmeria nivea L) by pyrite: Linking rhizosphere chemistry to plant metabolism - Tangshan Wu; Xiaofei Tan; Ping Chen; Chuang Li; Gaobin Chen; Zhenhong Huang; Genying Zeng; Yaqian Yang; Meijuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Fatty acid composition drives integrated changes in oxidative stability, phytonutrients and processing contaminants of diacylglycerols under thermal stress - Yingyi Zheng; Linjie Chen; Yee-Ying Lee; Mingchen Xu; Chin-Ping Tan; Yong Wang; Aijun Li; Zhen Zhang (Food Research International, 2026)

A fully biomass-derived intrinsically flame-retardant phenolic resin: Robust adhesion, fire-safe coatings, and closed-loop upcycling for multifunctional cellulose fibers - Wei Tan; Lei Tan; Yin Tian; Ying Chang; Guixiang Song; Lu Bai; Ping Li; Yuanlin Ren; Xiaohui Liu (Chemical Engineering Journal, 2026)

Regenerated cellulose fibers functionalized with lignin-derived boron-containing phenolic networks for durable flame retardancy and UV protection - Wei Tan; Jieyun Zhao; Lei Tan; Yin Tian; Guixiang Song; Ying Chang; Lu Bai; Ping Li; Yuanlin Ren; Xiaohui Liu (Carbohydrate Polymers, 2026)

“Precursors-in-action” nanoreactor: Coordination-activated self-assembly of cu/Fe bimetallic multifunctional metalloenzyme mimics for cascade-amplified breast cancer therapy - Peng Wang; Xin-Yi Zhang; Ying-Ying Han; Zhi-Yuan Li; Qing-Hua Shen; Long-Bo Yu; Cai-Ping Tan (Chemical Engineering Journal, 2026)

Advancing startup control procedures for enhanced reduction of persistent organic pollutant emissions from municipal solid waste incinerators - Nicholas Kiprotich Cheruiyot; Cindy Soo Yun Tan; Hsi-Hsien Yang; Kuan-Hsien Li; Syeda Seemab Naqvi; Mei-Jou Lu; Guo-Ping Chang-Chien; Lin-Chi Wang (Waste Management, 2026)

Orbitally driven ammonium upwelling fueled primary productivity during the peak Cambrian Explosion - Guangming Meng; Haifeng Gai; Chengang Lu; Yanming Zhao; Yineng Tan; Yang Liu; Yue Feng; Gang Li; Xing Wang; Wei Liu; Yijie Xing; Ping Gao; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Reactive nitrogen species-driven oxidative and nitrative damage underlying cadmium/mercury co-exposure: A multimodal fluorescent visualization study - Jiangkun Tan; Liangwei Zhang; Yunqing Wang; Xiaoyan Wang; Hongdan Wang; Ping Liu; Li Zhang; Jinmao You; Bing Yan; Lingxin Chen (Journal of Hazardous Materials, 2026)

Early Fibroblast Remodeling Associated with Lung Tissue Preservation After FLASH Irradiation - Caihui Li; Luhao Tan; Qixiang Liu; Zhihui Li; Menghua Li; Xuefeng Yang; Guofu Dong; Cheng Quan; Jie Ping; Changzhen Wang; Hao Lu (Phenomics, 2026)

Hydraulic connectivity of water-rich strata and directional drilling grouting for deep tunnel - Songtao Li; Yujie Wang; Ping Fu; Zhongsheng Tan; Qiang Lu; Xiaolong Pei (Journal of Mountain Science, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Market mechanism design and trading decision model incorporating renewable energy alliances for the future electricity capacity market of China - Ying-zhu Han; Xing-ping Zhang; Li Liu; Jia-lin Li; Qin-liang Tan; Yuan-fei Li; Yi Du (Energy Policy, 2026)

Facile preparation of new bidentate quaternary ammonium-type stationary phase for the separation of versatile analytes in hydrophilic interaction liquid chromatography - Xiao-dong Cheng; Kai-feng Tan; Cai-yong Lin; Yun-ping Li; Xue-xin Dai (Analytica Chimica Acta, 2026)

TGase-induced WPI-GA microgels for stabilized HIPEs and encapsulation probiotics with enhanced thermal stability and gastrointestinal survival - Yaxin Yin; Yingnan Zou; Chin Ping Tan; Deyang Li; Xiaojiao Zheng; Daodong Pan; Maolin Tu (Food Hydrocolloids, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Species-specific nutrient acquisition strategies in subtropical afforestation tree species under nitrogen fertilization - Sihui Qiu; Ying-Ping Wang; Shiting Xia; Songjia Chen; Jie Li; Zhongbing Chang; Mengxiao Yu; Yinping Tan; Ziqi Liang; Junhua Yan; Jun Jiang (Plant and Soil, 2026)

Insights into the size effect of Fe3O4 in Fe/AC for Hg0 removal and the corresponding mechanism - Jiawen Tan; Yuan Qin; Jiayi Piao; Zhao Li; Fei Wang; Ping Ning; Kai Li; Yixing Ma; Xin Sun (ENGINEERING Environment, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Distribution, fate, and risk prioritization of antibiotics in wastewater treatment plants in Northwest China: Insights into secondary sedimentation limitations and membrane process advantages - Yixi Zhang; Mengcheng Wu; Yunzhou Tan; Bo Du; Mengjiao Li; Liangliang Liu; Ping Wu; Guodong Kang; Shenghu Zhang; Zhengxiang Shi; Leilei Lu (Journal of Water Process Engineering, 2026)

Synergistic inspiration of in situ growth technology and biomass phytic acid for designing durable flame retardant and antibacterial cellulose fibers - Yin Tian; Wei Tan; Lu Bai; Lei Tan; Ying Chang; Guixiang Song; Ping Li; Yuanlin Ren; Xiaohui Liu (Carbohydrate Polymers, 2026)

MnO2/CNT-Modified Anode Microbial Fuel Cells for Removing Varying Amounts of Cu2+ from Wastewater - Jiahui Zhu; Lingling Li; Jun Zhou; Nasha Dou; Lei Gong; Mingjing Li; Hui Tan; Ping Yang; Wenfeng Wang (Water, Air, & Soil Pollution, 2026)

Cultivar-dependent effects of arbuscular mycorrhizal (AM) fungal inoculation on fruit quality and native AM fungal community in navel orange - Xin-Ping Tan; Cheng-Zhuo Li; Ying-Ning Zou; An-Qi Lei; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Green valorization of invasive alien plants using a novel method of simultaneous hydrothermal treatment and ball milling - Binglei Li; Yi Zhong; Chaoming Li; Xun Tan; Mingquan Lv; Shengjun Wu; Ping Huang; Zhilin Huang; Jiwei Bai; Zhong Chen (Biomass and Bioenergy, 2026)

Spring frost frequency increased in North America but decreased in Eurasia from 1948 to 2016 - Wei Guo; Chuhan Lu; Ping Xia; Lijiang Fu; Govindjee Govindjee; Hao Tang; Jian Chen; Li Song; Jinglu Tan; Zhenyu Xu; Ya Guo (Theoretical and Applied Climatology, 2026)

Metabolomic analysis of coloration mechanism of bamboo sheaths in different cultivars of Chimonobambusa utilis - Yan Lan; Xiao Zhu; Guang-Qian Gou; Ai-Juan Tan; Zhao-Xia Dai; Shi-Ping Huang; Gui-Li Yang (Physiology and Molecular Biology of Plants, 2026)

Plastome structure, repetitive sequences, and phylogeny of Orophea hainanensis (Annonaceae) - Jingyao Ping; Dong Tan; Aimin Li; Yangying Gan; Xianhai Zeng (Genetic Resources and Crop Evolution, 2026)

An efficient multi-objective optimization method for inter-basin water diversion based on the rotation vector method for exploring the convex objective space - Zekun Li; Bin Xu; Ping-an Zhong; Jiaying Tan; Ran Mo; Xinrong Wang; Zichen Ren; Guoqing Wang; Jianyun Zhang; Jiangyuan Li; Scott E. Boyce (Environmental Modelling & Software, 2026)

Fabrication of multifunctional cellulose aerogel materials with one-dimensional (fiber), two-dimensional (film), and three-dimensional (structure) structures based on ambient drying technology - Lei Tan; Wei Tan; Yin Tian; Guixiang Song; Ying Chang; Ping Li; Yuanlin Ren (Chemical Engineering Journal, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Measuring grazing grassland aboveground biomass and spatial heterogeneity based on UAV LiDAR observation with upscaling samples - Yu-Qing Wu; Li-Biao Guo; Wei-Xian Tan; Ping-Ping Huang; Ming-Ze Ma; Yang Zhao (International Journal of Remote Sensing, 2026)

Experimental and numerical study of a novel slope-type sliding isolation system for seismic protection of electrical equipment - Wanchen Meng; Yanhui Liu; Wenzhi Zheng; Ping Tan; Hao Li; Dengjie Zhu; Fubao Guo (Soil Dynamics and Earthquake Engineering, 2026)

Challenges and solutions to seismic amplitude pitfalls in dim-spot sandstone reservoirs: A case study from the Shaximiao formation, the Western Sichuan Depression, China - Feng Tan; Ping Yang; Jun-Xing Cao; Le Li; Zhihua Cui; Qian Ma (Journal of Applied Geophysics, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Integrated probabilistic forecasting framework for long-term reservoir outflow through dynamic coupling of meteorological–hydrological–engineering processes - Jiaying Tan; Bin Xu; Jian Zhu; Ping-an Zhong; Ran Mo; Jiangyuan Li; Yuanheng Dong; Xinman Qin; Jiayi Jiang; Huili Wang; Lingwei Zhu (Journal of Hydrology, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Fe2O3@diatomite heterogeneous fenton system for enhancing phosphorus bioavailability in dredged sediment - Wenmin Li; Jian Zhu; Pei Wu; Hongchun Huang; Xindeng Huang; Mengyan Wu; Ying Zhang; Kangrong Xiang; Jiangfeng Teng; Chang Sun; Ao Tan; Mingjing Lei; et al. (Journal of Environmental Chemical Engineering, 2025)

Simultaneously regulating the content of pores and carbon microcrystallites in carbon blocks via coal tar pitch oxygen functionalization for improved mechanical and wear resisting performance - Yixing Chen; Sihan Gao; Pei Gong; Ping Liu; Jiao Tan; Xun He; Hong Luo; Run Li; Chuanjun Tu (Fuel, 2025)

Effect of Accelerators on Hydrothermal Anaerobic Digestion of Platanus Orientalis Linn Fallen Leaves - Hui Tan; Hongyu Huo; Jun Zhou; Mingjing Li; Jiahui Zhu; Lei Gong; Wenfeng Wang; Ping Yang (Water, Air, & Soil Pollution, 2025)

Effect of fish skin gelatin on gluten proteins during freeze-thaw cycles - Mengjuan Li; Shangyuan Sang; Chin Ping Tan; Lijie Zhu; Xiaojuan Tang; Xin Zhang; Zixuan Yang; Xueming Xu (Journal of Cereal Science, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Electrospun Mn-doped ZIF-67 composite nanofibers with high water stability for efficient adsorption of antibiotics in aqueous systems - Xiaolin Yue; Can Cui; Shaolin Deng; Lan Wang; Ping Li; Anhong Li; Yizhong Zhang; Rui Hao; Wenyuan Tan (Journal of Environmental Chemical Engineering, 2025)

Cold crystallization-enabled permanent shape transformation in 4D-printed PLA/TPU composites for personalized wearable devices - Chuanru Zheng; Xi Li; Juan Tan; Anna Tan; Xiuchen Li; Hailiang Ni; Wenhao Yu; Yuefeng Bai; Ping Hu; Wei Min Huang; Hongmei Chen (Chemical Engineering Journal, 2025)

Economical and efficient production of l-norvaline using whole cells of Escherichia coli with an enzymatic cascade - Zimai Li; Qiaoyue Yang; Mingyuan Liu; Hairong Yu; Qihang Du; Hongxu Zhang; Jinglong Deng; Xiaoxu Tan; Weikang Sun; Tianyi Jiang; Qianjin Kang; Wensi Meng; et al. (Bioresource Technology, 2025)

Unveiling the vertical dynamics of atmospheric ammonium in Asia megacity: A GRASP-based investigation of spatiotemporal patterns and source drivers - Yining Tan; Ting Yang; Hongyi Li; Ping Tian; Yifan Song; Jiancun He; Yutong Tian; Yele Sun; Zifa Wang (Atmospheric Research, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Occurrence, molecular transformation and prioritizing environmental risks of organic nitrogen in aqueous phase from hydrothermal carbonization of waste activated sludge - Tingting Yang; Lichao Tan; Jiaqi Ge; Xue Zhang; Gang Zhou; Ping Li; Ninghui Song; Feng Ge (Journal of Hazardous Materials, 2025)

The deficiencies in texture, organic matter distribution, and active mineral composition of reservoir sediments constrain the formation of healthy soils - Xun Tan; Sidong Zeng; Binglei Li; Shengjun Wu; Ping Huang; Zhong Chen; Xingxing He; Zhilin Huang; Jiwei Bai (Journal of Environmental Management, 2025)

A novel damping adaptive pendulum isolation system for seismic resilience enhancement of continuous bridges - Wenzhi Zheng; Junliang Chen; Hao Wang; Ping Tan; Jian Li; Siqi Wang (Engineering Structures, 2025)

A three-dimensional model of two-phase flow to a horizontal well in dual-porosity media - Jie Hu; Ping Tan; Chen Sheng Zhang; He Li; Shun Jie Sun (Computers and Geotechnics, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

Field Tests Using High-Power Microwaves to Crack Iron Ore of Different Grades - Feng Lin; Xia-Ting Feng; Shi-Ping Li; Tian-Yang Tong; Yun-Tan Ao; Yu-Xi Liu (Rock Mechanics and Rock Engineering, 2025)

Genomic selection for hard-to-measure traits in aquaculture: Challenges in balancing genetic gain and diversity - Ziyi Kang; Jie Kong; Qi Li; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Zhaoxin Wang; et al. (Aquaculture, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Highly selective conversion of NO to NO3—through radical modulation over UiO-66–67-NH2 S-scheme heterojunction - Ping Tan; Zhuo Wang; Zhen Mao; Riming Hu; Jiayuan Yu; Yuhan Li (Journal of Hazardous Materials, 2025)

Dose-dependent effects of MIL-88A(Fe) and MIL-101(Fe) on arsenic immobilization and phytoremediation using ramie (Boehmeria nivea L.) - Jian Ye; Xingyan Yin; Chunping Yang; Xiaofei Tan; Chuang Li; Gaobin Chen; Ping Chen; Qiang Chen; Mingyang Dai (Chemical Engineering Journal, 2025)

A leader-follower contrastive learning framework for imbalanced multimodal remote sensing image classification - Jia Li; Lin Zhao; Ping Tan; Minhui Zhao; Guoyun Zhang; Xinping Li (International Journal of Remote Sensing, 2025)

Investigating the pyrolysis of large biomass particle streams in CO2/H2O atmosphere at high heating rates: A modeling approach - Jiaye Zhang; Xiangdong Li; Hui Lin; Stephan Heberlein; Wei Ping Chan; Xuebin Wang; Houzhang Tan; Grzegorz Lisak (Fuel, 2025)

Unveiling the intricate dynamics of PM2.5 sulfate aerosols in the urban boundary layer: A pioneering two-year vertical profiling and machine learning-enhanced analysis in global Mega-City - Hongyi Li; Ting Yang; Yifan Song; Ping Tian; Jiancun He; Yining Tan; Yutong Tian; Yele Sun; Zifa Wang (Urban Climate, 2025)

Five undescribed chromone-phenylpyridone hybrids from Cineraria repanda-derived Penicillium oxalicum with cytotoxic and antibacterial activity - Yu Wei Huang; Jing Guan; Yin Tang; Ren Xiang Tan; Li Ping Lin (Phytochemistry, 2025)

Insight into the influence of slight air oxidation on the carbonization behavior of pitch/calcined coke mixture to deliver high-performance graphite blocks - Pei Gong; Chongwei Li; Jiao Tan; Ping Liu; Xun He; Yixing Chen; Xiaobin Zeng; Run Li; Chuanjun Tu (Fuel, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Validation of Interaction Between Sugarcane miR167d and Predicted Target Gene ScPUM1 and Analysis of Their Expression Under Cold Stress: A Novel Mechanism of miR167d - Qiqi Song; Pengjin Zhu; Jiahui Li; Qin Cheng; Qinliang Tan; Quanguang Zhou; Ping Lv; Zemei Nong (Journal of Plant Growth Regulation, 2025)

Preparation of electrospun ZIF-67/PVP/PVDF composite nanofiber membranes for efficient tetracycline removal from water - Shaolin Deng; Jing Zhang; Xiaolin Yue; Ping Li; Anhong Li; Zehua Huang; Wenyuan Tan (Journal of Environmental Chemical Engineering, 2025)

Genomic selection of resistance to acute hepatopancreatic necrosis disease in Litopenaeus vannamei - Mianyu Liu; Xupeng Li; Jie Kong; Xianhong Meng; Kun Luo; Juan Sui; Ping Dai; Jian Tan; Jiawang Cao; Baolong Chen; Hongjie Wang; Sheng Luan (Aquaculture, 2025)

Effects of polyunsaturated fatty acid and diacylglycerol on the crystallization behaviors of palm-based oil - Wanting Ke; Yee-Ying Lee; Chin-Ping Tan; Aijun Li; Yufei Zhang; Yong Wang; Zhen Zhang (Food Chemistry, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Responses of microbial communities to the addition of different types of microplastics in agricultural soils - Ke Li; Qihao He; Jian Zhu; Jieying Wang; Chang Sun; Ao Tan; Xiaoqi Zhao; Yuanhao Peng; Chao Huang; Jingju Cai; Ping Wang; Zhiming Liu (Environmental Pollution, 2025)

PB@COF-derived core–shell Fe/Fe3O4/C composites with excellent electromagnetic wave absorption performance for the entire Ku band - Gang Li; Ruiyang Tan; Bohong Gao; Xinli Liu; Mingyuan Zhang; Ping Chen; Xinyi Wang (Chemical Engineering Journal, 2025)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

Model the evolutionary pattern of N species and pool size in groundwater continuum by utilizing measured source and sink rates of nitrate and ammonium - Li-Li Han; Lianghao Ge; Ehui Tan; Wenbin Zou; Li Tian; Ping Li; Min Nina Xu; Shuh-Ji Kao (Journal of Hazardous Materials, 2024)

Dynamic high pressure microfluidization modified oat dietary fiber: Texture modulation and its mechanistic in whole grain oat milk - Ziyue Kang; Ning Meng; Ming Liu; Yanxiang Liu; Ping Jiang; Xiaotong Zhai; Yanan Fei; Li Wang; Juanli Shen; Bin Tan (Food Hydrocolloids, 2024)

Pyrite functionalized Black Soldier Fly feces biochar for mine soil quality improvement and heavy metals immobilization - Chuang Li; Lei Zhao; Ping Chen; Shujing Ye; Hailan Yang; Yanling Gu; Shaobo Liu; Zhiming Yang; Xinjiang Hu; Xiaofei Tan (Process Safety and Environmental Protection, 2024)

Framework for lifecycle resilience assessment of earthquake-damaged coastal RC structures considering non-uniform corrosion - Zhiruo Yang; Yiming Li; Ping Tan; JingZhou Zhang (Ocean Engineering, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Fe-reinforced silkworm silk with superstrong mechanical properties for mass production - Qingsong Liu; Xin Wang; Yifan Zhou; Yi Li; Zhangchuan Peng; Zhangchen Tang; Xiangyu Cai; Xinyu Fan; Xin Tang; Xiaoyin Tan; Xiaoqian Xie; Xinning Li; et al. (Chemical Engineering Journal, 2024)

Electrical structure identification of deep shale gas reservoir in complex structural area using wide field electromagnetic method - Zhi-Wen Gu; Yue-Gang Li; Chang-Heng Yu; Zhong-Ping Zou; Ai-Guo Hu; Xue-Bo Yin; Qinag Wang; Heng Ye; Zhang-Kun Tan (Applied Geophysics, 2024)

Two pairs of new isobenzofuranone enantiomers from a soil-derived fungus Penicillium canescens DWS225 - Jing Wang; Xiao-Qian Wu; Ji-Song Mo; Yu-Fen Tan; Hong-Ping Long; Si-Qian Zhou; Shao Liu; Jing Li; Wen-Xuan Wang (Natural Product Research, 2024)

Deciphering the influence of salinity stress on the biological aniline degradation system: Pollutants degradation performance and microbial response - Qi He; Bin Tan; Meng Li; Junhao Su; Bing Lin; Nan-ping Wu; Hao-nan Shen; Jia-jing Chen; Qian Zhang (Environmental Research, 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

Assessment and measurement of ground motion risk levels for structures isolated by double concave friction pendulum system - Jiaxi Li; Ping Tan; Kui Yang (Soil Dynamics and Earthquake Engineering, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Physicochemical characteristics of grease-trap wastewater with different potential mechanisms of FOG solid formation, separation, and accumulation inside grease traps - Ling Ying Tang; Ngie Hing Wong; Thion Am Chieng; Alex Kwong Jun Kiu; Chung Siung Choo; Yali Li; Chin Ping Tan; Abu Zahrim Yaser; Deni Shidqi Khaerudini; Gui Hua Chen; Jaka Sunarso (Water Research, 2024)

Experimental study and numerical model of a new passive adaptive isolation bearing - Siqi Wang; Yong Yuan; Ping Tan; Yafeng Li; Wenzhi Zheng; Dehong Zhang (Engineering Structures, 2024)

Culture of cerebrospinal fluid-contacting neurons from neonatal mouse spinal cord - Liang Cao; Hui-Qian Zhang; Yu-Qi He; Ping-Jiang An; Lei-Luo Yang; Wei Tan; Gang Liu; Chun-Qing Wang; Xiao-Wei Dou; Qing Li (Cell and Tissue Banking, 2024)

Effect of the CYBA C242T Polymorphism on Preeclampsia Pathogenesis in the Chinese Population - Ru Zhang; Shuhui Liu; Ping Tan; Zihan Guo; Huabin Hou; Shiguo Liu; Hui Li; Xibing Wang (Biochemical Genetics, 2024)

Optimal open nucleus breeding system for long-term genetic gain in the Pacific white shrimp using genomic selection - Ziyi Kang; Jie Kong; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Junyu Liu; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Qi Li; et al. (Aquaculture, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Correlation of Immune-Inflammatory Response System (IRS)/Compensatory Immune-Regulatory Reflex System (CIRS) with White Matter Integrity in First-Episode Patients with Schizophrenia - Mengzhuang Gou; Wei Li; Jinghui Tong; Yanfang Zhou; Ting Xie; Ting Yu; Wei Feng; Yanli Li; Song Chen; Baopeng Tian; Shuping Tan; Zhiren Wang; et al. (Molecular Neurobiology, 2024)

Improved response spectrum analysis procedure for an adaptive variable friction pendulum isolated structure considering frictional dependency - Kui Yang; Ping Tan; Jiying Shang; Huating Chen; Jiaxi Li; Yue Xiang; Yafeng Li (Soil Dynamics and Earthquake Engineering, 2024)

Insights into the differences in metal anchoring mechanisms and the impact on HCN catalytic oxidation performance - Zhao Li; Jiawen Tan; Yuxuan Xie; Xinyu Yang; Chunxue Wang; Kai Li; Ping Ning; Fei Wang (Fuel, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Optimization of water and fertilizer management of Panax pseudoginseng based on changes in soil microbial biomass carbon and nitrogen and enzyme activities - Yunfei Tuo; Hao Tan; Jiaping Liang; Jianqiang Li; Ping Xiang; Qiliang Yang; Xiahong He (Applied Soil Ecology, 2024)

Exploring the antiviral potential of paeonol from medicinal plants: A promising strategy for controlling white spot syndrome virus - Cheng Chen; Chang-Shuai Liang; Xiang-Yu Qu; Peng-Fei Li; Xiao-Ping Tan; Fei Ling; Gao-Xue Wang (Aquaculture, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

A framework for nonlinear peak response evaluation from linear response spectra of base-isolated structures using the bilinear hysteretic model - Kui Yang; Ping Tan; Huating Chen; Jiaxi Li; Wenzhi Zheng (Soil Dynamics and Earthquake Engineering, 2024)

Biodegradation properties and mechanism of triketone herbicide mesotrione via newly isolated bacterium Klebsiella pasteurii CM-1 - Xiaotian Cao; Yuanfu Li; Wei Liu; Ning Hou; Feng Zhao; Ping Han; Huihua Tan (International Biodeterioration & Biodegradation, 2024)

Physical, textural and crystallization properties of ground nut oil-based diacylglycerols in W/O margarine system - Wanting Ke; Yee-Ying Lee; Jianqiang Cheng; Chin-Ping Tan; Oi-Ming Lai; Aijun Li; Yong Wang; Zhen Zhang (Food Chemistry, 2024)

Deciphering the role of hydraulic retention time (HRT) in integrated fixed-film activated sludge (IFAS) system under aniline stress: Effects on microbial succession and communication - Nan-ping Wu; Bin Tan; Meng Li; Naif Abdullah Al-Dhabi; Bing Lin; Qi He; Hao-nan Shen; Jia-jing Cheng; Wangwang Tang; Qian Zhang (Chemical Engineering Journal, 2024)

The effect of an improved passive bumper on the seismic response of the base-isolated structure: Numerical simulations and optimization design - Weijian Zhong; Binbin Li; Yanhui Liu; Ping Tan; Fulin Zhou (Soil Dynamics and Earthquake Engineering, 2024)

Optimal design of tuned inerter negative stiffness dampers with linear viscous and nonlinear eddy current damping for structural effective damping ratio enhancement - Yafeng Li; Ping Tan; Siqi Wang; Shouying Li; Xianxiong Zhang (Soil Dynamics and Earthquake Engineering, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Phenolic and bisamide derivatives from Aglaia odorata and their biological activities - Xiaomeng Yang; Yan Yu; Panfeng Wu; Juan Liu; Yanan Li; Linlan Tao; Rong Tan; Xiaojiang Hao; Chunmao Yuan; Ping Yi (Natural Product Research, 2023)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Sediment depth-related variations of comammox Nitrospira: Evidence in the Three Gorges Reservoir, China - Baohong Yu; Quanchao Zeng; Jinlin Li; Jun Li; Xun Tan; Xin Gao; Ziqiang Mao; Ping Huang; Shengjun Wu (Science of The Total Environment, 2023)

Formation of the V-shaped conjugate strike-slip faults revealed by crustal anisotropy in the central Tibetan Plateau - Shitan Nie; Jiangtao Li; Chenglong Wu; Ping Tan (Journal of Asian Earth Sciences, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Vertical variation in prokaryotic community composition and co-occurrence patterns in sediments of the Three Gorges Reservoir, China - Baohong Yu; Quanchao Zeng; Jinlin Li; Jun Li; Xun Tan; Xin Gao; Ping Huang; Shengjun Wu (Environmental Research, 2023)

Seismic design and experimental testing of precast tolerance concrete shear wall subject to cyclic load - Peng Mi; Ping Tan; Yiming Li; Zhibin Liu; Mengxiong Tang; Fulin Zhou (Engineering Structures, 2023)

Soil depths and developmental stages of biological soil crusts are more important than shrub cover in structuring prokaryotic communities - Lin Xu; Yongping Kou; Wenjun Xiong; Chaonan Li; Ping Zou; Bingjie Jiao; Zhenfeng Xu; Bo Tan; Minjie Yao; Bingchang Zhang; Xiangzhen Li (CATENA, 2023)

Persulfate activation with nitrogen and sulfur co-doped porous biochar to remove thiamethoxam: A combination of radicals and nonradicals - Ziqi Wang; Xiangyu Meng; Yewen Yang; Honghui Jiang; Xinyuan Tan; Jingju Cai; Meifang Li; Ke Ouyang; Tingting Li; Ping Wang; Hui Wang; Xinjiang Hu (Journal of Environmental Chemical Engineering, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

The seasonal patterns of aquatic insect composition and diversity in a disturbed (sub)tropical river revealed by linear and nonlinear approaches with occurrence and abundance data - Lu Wang; Yaokai Li; Jiaxu Li; Lin Tan; Eric Zeus Rizo; Bo-Ping Han (Hydrobiologia, 2023)

Spatiotemporal distribution, sources apportionment and ecological risks of PAHs: a study in the Wuhan section of the Yangtze River - Yulin Chen; Ranran Song; Ping Li; Yile Wang; Yang Tan; Yongfei Ma; Lie Yang; Li Wu; Zhenjie Du; Xuebin Qi; Zulin Zhang (Environmental Geochemistry and Health, 2023)

Genome-wide DNA methylation analysis in schizophrenia with tardive dyskinesia: a preliminary study - Ping Zhang; Yongke Lu; Yanli Li; Kesheng Wang; Huimei An; Yunlong Tan (Genes & Genomics, 2023)

Crustal structure of the Tibetan Plateau and adjacent areas revealed from ambient noise tomography - Ping Tan; Xiaofeng Liang; Wei Li; Chenglong Wu (Gondwana Research, 2023)

Liver-cell protective pyridones from the fungi Tolypocladium album dws120 - Xiao-Qian Wu; Jing Li; Xi Zhou; Jing Wang; Yu-Fen Tan; Ji-Song Mo; Shao Liu; Kang-Ping Xu; Gui-Shan Tan; Wei Zhang; Wen-Xuan Wang (Phytochemistry, 2023)

Rat Hair Metabolomics Analysis Reveals Perturbations of Unsaturated Fatty Acid Biosynthesis, Phenylalanine, and Arachidonic Acid Metabolism Pathways Are Associated with Amyloid-β-Induced Cognitive Deficits - Tian-Hoe Tan; Shih-Wen Li; Chih-Wei Chang; Yuan-Chih Chen; Yu-Hsuan Liu; Jui-Ti Ma; Ching-Ping Chang; Pao-Chi Liao (Molecular Neurobiology, 2023)
Hair is a noninvasive valuable biospecimen for the long-term assessment of endogenous metabolic disturbance. Whether the hair is suitable for identifying biomarkers of the Alzheimer’s disease (AD) process remains unknown. We aim to investigate the metabolism changes in hair after β-amyloid (Aβ 1-42 ) exposure in rats using ultra-high-performance liquid chromatography-high-resolution mass spectrometry–based untargeted and targeted methods. Thirty-five days after Aβ 1-42 induction, rats displayed significant cognitive deficits, and forty metabolites were changed, of which twenty belonged to three perturbed pathways: (1) phenylalanine metabolism and phenylalanine, tyrosine, and tryptophan biosynthesis— l -phenylalanine, phenylpyruvate, ortho-hydroxyphenylacetic acid, and phenyllactic acid are up-regulated; (2) arachidonic acid (ARA) metabolism—leukotriene B4 (LTB4), arachidonyl carnitine, and 5(S)-HPETE are upregulation, but ARA, 14,15-DiHETrE, 5(S)-HETE, and PGB2 are opposite; and (3) unsaturated fatty acid biosynthesis— eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), FA 18:3 + 1O, and FA 18:3 + 2O are downregulated. Linoleic acid metabolism belonging to the biosynthesis of unsaturated fatty acid includes the upregulation of 8-hydroxy-9,10-epoxystearic acid, 13-oxoODE, and FA 18:2 + 4O, and downregulation of 9(S)-HPODE and dihomo-γ-linolenic acid. In addition, cortisone and dehydroepiandrosterone belonging to steroid hormone biosynthesis are upregulated. These three perturbed metabolic pathways also correlate with cognitive impairment after Aβ 1-42 stimulation. Furthermore, ARA, DHA, EPA, l -phenylalanine, and cortisone have been previously implicated in the cerebrospinal fluid of AD patients and show a similar changing trend in Aβ 1-42 rats’ hair. These data suggest hair can be a useful biospecimen that well reflects the expression of non-polar molecules under Aβ 1-42 stimulation, and the five metabolites have the potential to serve as novel AD biomarkers.

Using Protection Motivation Theory to examine information-seeking behaviors on climate change - Jun Li; Ping Qin; Yifei Quan; Jie-Sheng Tan-Soo (Global Environmental Change, 2023)

Enhanced self-sintering mechanical strength of carbon blocks via removal of light molecular-weight compound in green petroleum coke - Jiao Tan; Ping Liu; Pei Gong; Yanli Liu; Jian Chen; Run Li; Chuanjun Tu (Fuel, 2023)

Integrated fixed-film activated sludge systems in continuous-flow and batch mode acclimated from low to high aniline concentrations: Performance, mechanism and metabolic pathways - Nan-ping Wu; Qian Zhang; Bin Tan; Meng Li; Bing Lin; Jing He; Jun-hao Su; Hao-nan Shen (Bioresource Technology, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Neuroprotective methylsuccinic acid and enoic acid derivatives from the fungus Xylaria longipes - Jing Li; Yu-Fen Tan; Si-Qian Zhou; Shao Liu; Wen-Xuan Wang; Yue-Ping Jiang; Hong-Ping Long; Ji-Kai Liu (Phytochemistry, 2023)

Structured lipids produced from palm-olein oil by interesterification: A controllable lipase-catalyzed approach in a solvent-free system - Hongzeng Ai; Yee-Ying Lee; Xiaodong Xie; Chin Ping Tan; Oi Ming Lai; Aijun Li; Yong Wang; Zhen Zhang (Food Chemistry, 2023)

A novel tuned inerter eddy current damper: modeling, optimization, and evaluation - Yafeng Li; Ping Tan; Shouying Li; Hui He (Engineering Structures, 2023)

Superelastic pendulum isolator with multi-stage variable curvature for seismic resilience enhancement of cold-regional bridges - Wenzhi Zheng; Ping Tan; Jian Li; Hao Wang; Yanhui Liu; Zhibin Xian (Engineering Structures, 2023)

Chemosensory proteins are associated with thiamethoxam tolerance in bird cherry-oat aphid Rhopalosiphum padi - Ping Gao; Siqian Zhang; Junjie Tan; Xinghao Li; Maohua Chen (Pesticide Biochemistry and Physiology, 2023)

NH3 and N2O emission durability of the heavy-duty diesel engine with DOC, DPF, SCR, and ASC through the accelerated aging method - Liqun Lyu; Wenqiang Sun; Ping Feng; Huaiyu Wang; Lijun Hao; Jianwei Tan; Xin Wang; Chao Song; Haixia Li; Zhao Li; Jiaxing Wang; Yunshan Ge (Fuel, 2023)

Uncovering acid resistance genes in lactic acid bacteria and impact of non-viable bacteria on bacterial community during Chinese strong-flavor baijiu fermentation - Xinyue Li; Guangxun Tan; Ping Chen; Kaiyun Cai; Weiwei Dong; Nan Peng; Shumiao Zhao (Food Research International, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Molybdenum isotope evidence from restricted-basin mudstones for an intermediate extent of oxygenation in the late Ediacaran ocean - Zhaozhao Tan; Jinxiang Wu; Wanglu Jia; Jie Li; Brian Kendall; Jianzhong Song; Ping’an Peng (Chemical Geology, 2023)

Fast asteroidal period inversion by parallel acceleration-based three-step reduced voting - Yong-Xiong Zhang; Xiao-Ping Lu; Tan Guo; Xin-Ran Li (Advances in Space Research, 2023)

Seismic behavior of unbonded post-tension wall with replaceable energy dissipator - Peng Mi; Ping Tan; Yiming Li; Xiaofeng Zhao; Mengxiong Tang (Soil Dynamics and Earthquake Engineering, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Transcriptome sequencing reveals neurotoxicity in embryonic neural stem/progenitor cells under heat stress - Zeze Wang; Xue Luo; Zhen Luo; Yulong Tan; Genlin He; Ping Li; Xuesen Yang (Toxicology in Vitro, 2023)

First discovery of biodegraded petroleum in the South Qilian Basin, Northwest China: Implications for the origin of gas hydrates - Furong Tan; Yang Li; Yigui Han; Guochun Zhao; Shiming Liu; Fangpeng Du; Zhiqing Xie; Ping Lu (Journal of Asian Earth Sciences, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Seismic performance upgrading of bridges using superelastic pendulum isolators with variable stiffness considering temperature effects - Wenzhi Zheng; Ping Tan; Jian Li; Hao Wang; Yanhui Liu; Kui Yang (Engineering Structures, 2023)

Dysfunction of DNA repair for boosted tumor cell cycle arrest based on NIR-II biodegradable Te-prussian blue nanorod - Xiaoyang Liang; Ping Liu; Wen Li; Long Binh Vong; Tingting Wang; Lujing Geng; Yue Zhou; Siyu Wang; Qiang Lu; Fengping Tan; Xinxing Wang; Nan Li (Chemical Engineering Journal, 2023)

Interacting polymer-modification enzymes in heparan sulfate biosynthesis - Tianji Zhang; Mingjia Yu; Honglian Li; Marco Maccarana; Wei Zhang; Deling Shi; Ying Kan; Xiao Zhang; Lianli Chi; Ulf Lindahl; Hongmei Li; Jin-ping Li; et al. (Carbohydrate Polymers, 2023)

c-kit+VEGFR-2+ Mesenchymal Stem Cells Differentiate into Cardiovascular Cells and Repair Infarcted Myocardium after Transplantation - Pei Zhou; Shu-na Yu; Hai-feng Zhang; Yong-li Wang; Ping Tao; Yu-zhen Tan; Hai-jie Wang (Stem Cell Reviews and Reports, 2023)
Resent study suggests that c-kit + cells in bone marrow-derived MSCs may differentiate toward cardiamyocytes. However, the properties of c-kit + MSCs remain unclear. This study isolated c-kit + VEGFR-2 + cells from rat bone marrow-derived MSCs, and assessed potential of c-kit + VEGFR-2 + MSCs to differentiate towards cardiovascular cells and their efficiency of repairing the infarcted myocardium after transplantation. Gene expression profile of the cells was analyzed with RNA-sequencing. Potential of differentiation of the cells was determined after induction. Rat models of myocardial infarction were established by ligation of the left anterior descending coronary artery. The cells were treated with hypoxia and serum deprivation for four hours before transplantation. Improvement of cardiac function and repair of the infarcted myocardium were assessed at four weeks after transplantation. Gene expression profile revealed that c-kit + VEGFR-2 + MSCs expressed most smooth muscle-specific and myocardium-specific genes, while expression of endothelium-specific genes was upregulated significantly. After induction with VEGF or TGF-β for two weeks, the cells expressed CD31 and α-SMA respectively. At three weeks, BMP-2-induced cells expressed cTnT. After transplantation of the cells, cardiac function was improved, scar size of the infarcted myocardium was decreased, and angiogenesis and myocardial regeneration were enhanced significantly. Moreover, paracrine in the myocardium was increased after transplantation. These results suggest that c-kit + VEGFR-2 + MSCs have a potential of differentiation towards cardiovascular cells. Transplantation of c-kit + VEGFR-2 + MSCs is effective for repair of the infarcted myocardium. c-kit + VEGFR-2 + MSCs may be a reliable source for cell therapy of ischaemic diseases. Graphical abstract

Knockdown of lncRNA-ASLNC12002 alleviates epithelial–mesenchymal transition of type II alveolar epithelial cells in sepsis-induced acute respiratory distress syndrome - Kaixuan Feng; Weifeng Huang; Jiawei Shang; Feng Ping; Qin Tan; Wei Wang; Yingchuan Li; Yongmei Cao (Human Cell, 2022)
Patients with sepsis-induced acute respiratory distress syndrome (ARDS) have higher mortality and poor prognosis than pneumonia-induced ARDS. Pulmonary fibrosis is an irreversible accumulation of connective tissue in the interstitium of the lung and closely associated with the epithelial–mesenchymal transition (EMT) of type II alveolar epithelial cells (AECIIs). Therefore, it is undoubtedly worth studying whether the EMT of AECIIs in sepsis-induced ARDS patients is different from that in patients with pneumonia-induced ARDS in the regulatory mechanism. Here, we will report for the first time that an lncRNA-ASLNC12002 is highly expressed in AECIIs of patients with sepsis-induced pneumonia and promotes EMT in AECIIs. The research results showed that the expression of ASLNC12002 in AECIIs derived from patients with sepsis-induced ARDS is significantly higher than that in normal people and pneumonia-induced ARDS patients. Mechanism research showed that ASLNC12002 can cause the inactivation of the anti-EMT pathway NR2F2/miR128-3p/Snail1 by acting as the sponge of miR128-3p. Functional experiments showed that targeted silencing of ASLNC12002 could effectively inhibit EMT progression in AECIIs of patients with sepsis-induced pneumonia by restoring NR2F2/miR128-3p/Snail1 pathway. In a word, our study shows for the first time that the inactivation of NR2F2/miR128-3p/Snail1 pathway caused by the enhanced expression of ASLNC12002 is the direct reason why AECIIs in sepsis-induced ARDS patients are prone to get EMT progress. ASLNC12002 has the potential to become a biological target for the prevention and treatment of pulmonary fibrosis in patients with sepsis-induced ARDS. At the same time, the expectation that ASLNC12002 and its related products may be used as clinical markers for the evaluation of early pulmonary fibrosis in ARDS patients should not be ignored.

Joint effect of East Asia–Pacific and Scandinavian teleconnections on summer precipitation in Southwest China - Yang Mingxin; Xiao Tiangui; Zhao Ping; Li Yong; Huang Wei; Li Yueqing; Tan Jie (Theoretical and Applied Climatology, 2022)
Based on the summer precipitation data from 328 meteorological stations in Southwest China and the monthly mean reanalysis data from the National Centers for Environmental Prediction/National Center for Atmospheric Research, the relationships of summer precipitation in Southwest China with the East Asia–Pacific (EAP) teleconnection pattern and the Scandinavian (SCA) teleconnection pattern are explored by using correlation analysis and composite analysis. The results show that the two teleconnections are significantly negatively correlated with the summer precipitation in Southwest China in the same period. The EAP teleconnection pattern and the SCA teleconnection pattern can affect the summer precipitation in Southwest China by affecting the atmospheric circulation situation in the middle and high latitudes, the north–south and east–west movement of the WPSH, and the water vapor transport in southwest China. In particular, the EAP and SCA teleconnections jointly affect the summer precipitation in Southwest China, which can be divided into four categories of configurations based on their phases, that is, (I) positive EAP + positive SCA, (II) negative EAP + negative SCA, (III) positive EAP + negative SCA, and (IV) negative EAP + positive SCA. The distribution of summer precipitation in Southwest China varies under different categories of configurations. Category I (II) corresponds to an opposite distribution pattern of precipitation anomalies between the north and south of Southwest China. In the configuration of category I(II), the cold air from high latitudes is weaker (stronger), the WPSH is more north(south) and more west(east) than the climatological mean, and the water vapor mainly comes from the Western Pacific (Bay of Bengal), thus resulting in category I(II), the opposite distribution of precipitation. While for configuration of category III(IV), no similar symmetrical distribution of precipitation anomalies can be found, and no obvious other distribution characteristics as well.

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Rapid triage for ischemic stroke: a machine learning-driven approach in the context of predictive, preventive and personalised medicine - Yulu Zheng; Zheng Guo; Yanbo Zhang; Jianjing Shang; Leilei Yu; Ping Fu; Yizhi Liu; Xingang Li; Hao Wang; Ling Ren; Wei Zhang; Haifeng Hou; et al. (EPMA Journal, 2022)
Background Recognising the early signs of ischemic stroke (IS) in emergency settings has been challenging. Machine learning (ML), a robust tool for predictive, preventive and personalised medicine (PPPM/3PM), presents a possible solution for this issue and produces accurate predictions for real-time data processing. Methods This investigation evaluated 4999 IS patients among a total of 10,476 adults included in the initial dataset, and 1076 IS subjects among 3935 participants in the external validation dataset. Six ML-based models for the prediction of IS were trained on the initial dataset of 10,476 participants (split participants into a training set [80%] and an internal validation set [20%]). Selected clinical laboratory features routinely assessed at admission were used to inform the models. Model performance was mainly evaluated by the area under the receiver operating characteristic (AUC) curve. Additional techniques—permutation feature importance (PFI), local interpretable model-agnostic explanations (LIME), and SHapley Additive exPlanations (SHAP)—were applied for explaining the black-box ML models. Results Fifteen routine haematological and biochemical features were selected to establish ML-based models for the prediction of IS. The XGBoost-based model achieved the highest predictive performance, reaching AUCs of 0.91 (0.90–0.92) and 0.92 (0.91–0.93) in the internal and external datasets respectively. PFI globally revealed that demographic feature age, routine haematological parameters, haemoglobin and neutrophil count, and biochemical analytes total protein and high-density lipoprotein cholesterol were more influential on the model’s prediction. LIME and SHAP showed similar local feature attribution explanations. Conclusion In the context of PPPM/3PM, we used the selected predictors obtained from the results of common blood tests to develop and validate ML-based models for the diagnosis of IS. The XGBoost-based model offers the most accurate prediction. By incorporating the individualised patient profile, this prediction tool is simple and quick to administer. This is promising to support subjective decision making in resource-limited settings or primary care, thereby shortening the time window for the treatment, and improving outcomes after IS.

Trichocladabiflavone A, a chalcone-flavonone type biflavonoid from Selaginella trichoclada Alsto - Yang Xie; Xiao-Chang Yao; Lei-Hong Tan; Hong-Ping Long; Ping-Sheng Xu; Jing Li; Gui-Shan Tan (Natural Product Research, 2022)

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

Microplastic Contamination on the Beaches of South China - Bingwen Chai; Yanping Li; Li Wang; Xiao-Tan Zhang; Yi-Ping Wan; Fengyuan Chen; Jie Ma; Wenlu Lan; Ke Pan (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. The sandy beach is a fragile environment that deserves our special attention with regard to MP contamination, as this area is a hotspot that accumulates large quantities of plastic waste. Notably, our current understanding of the MP distribution on beaches and the scale of contamination is far from sufficient. Hence, this study investigated the occurrence and characteristics of MPs on 14 beaches along the coast of South China. The MPs were ubiquitously distributed in the sand, most were small, less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting that diverse types of MPs are present on the beaches. Polyethylene, polypropylene, and polystyrene were the dominant types of MPs in most of our sampling sites. The MP abundance was higher in the upper layers (0–20 cm) of the beach than in the deeper layers (20–40 cm) of the sampling site when characterized by depth (Yangjiang beach). Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More effort is needed to clarify the vertical distribution of MPs on beaches, especially for those MPs less than 1 μm.

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Seven new glycosides from the leaves of Datura metel L. - Jin-Yan Tan; Yan Liu; Yan-Gang Cheng; Yan-Ping Sun; Xiao-Mao Li; Wei Guan; Juan Pan; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Retraction Note to: Deoxynivalenol-induced alterations in the redox status of HepG2 cells: identification of lipid hydroperoxides, the role of Nrf2-Keap1 signaling, and protective effects of zinc - Wageh Sobhy Darwish; Zhen Chen; Yonghan Li; Hui Tan; Hitoshi Chiba; Shu-Ping Hui (Mycotoxin Research, 2021)

Two new biflavanoids from Selaginella trichoclada Alsto - Yang Xie; Ping-Sheng Xu; Kang-Ping Xu; Zhen-Xing Zou; Gan Zhou; Dai Li; Dan Li; Xiao-Min Li; Jing Li; Gui-Shan Tan (Natural Product Research, 2021)

Design, synthesis, and antidepressant/anticonvulsant activities of 3H-benzo[f]chromen chalcone derivatives - Qiu-Wan Tan; Li-Ya He; Zhi-Wen He; Wei-Hua Liu; Shan-Shan Zhang; Lin Lin; Hong-Li Yang; Li-Ping Guan (Medicinal Chemistry Research, 2021)

Metabolic cold adaptation in the Asiatic toad: intraspecific comparison along an altitudinal gradient - Song Tan; Ping Li; Zhongyi Yao; Gaohui Liu; Bisong Yue; Jinzhong Fu; Jingfeng Chen (Journal of Comparative Physiology B, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Taxonomic reassessment of Polysiphonia hainanensis (Rhodomelaceae, Rhodophyta) based on molecular and morphological analyses - Huaqiang Tan; Wenhua Liu; Ping Li (Journal of Oceanology and Limnology, 2021)

New cytotoxic biflavones from Selaginella doederleinii - Li-Fei Liu; Hui-Hui Sun; Jian-Bing Tan; Qi Huang; Fei Cheng; Kang-Ping Xu; Zhen-Xing Zou; Gui-Shan Tan (Natural Product Research, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Antimonate removal by diatomite modified with Fe-Mn oxides: application and mechanism study - Qiu-Yi Dong; Yu-Chun Fang; Bin Tan; Aura Ontiveros-Valencia; Ang Li; He-Ping Zhao (Environmental Science and Pollution Research, 2021)

Comparison of Long-Term Outcomes of Endoscopic and Minimally Invasive Catheter Evacuation for the Treatment of Spontaneous Cerebellar Hemorrhage - Leiyang Li; Haixiao Liu; Jianing Luo; Zhijun Tan; Junmei Gao; Ping Wang; Wenting Jing; Ruixi Fan; Xiaoyang Zhang; Hao Guo; Hao Bai; Wenxing Cui; et al. (Translational Stroke Research, 2021)
Recently, minimally invasive techniques, including endoscopic evacuation and minimally invasive catheter (MIC) evacuation, have been used for the treatment of patients with spontaneous cerebellar hemorrhage (SCH). However, credible evidence is still needed to validate the effects of these techniques. To explore the long-term outcomes of both surgical techniques in the treatment of SCH. Fifty-two patients with SCH who received endoscopic evacuation or MIC evacuation were retrospectively reviewed. Six-month mortality and the modified Rankin Scale (mRS) score were the primary and secondary outcomes, respectively. A multivariate logistic regression model was used to assess the effects of the different surgical techniques on patient outcomes. In the present study, the mortality rate for the entire cohort was 34.6%. Univariate analysis showed that the surgical technique and preoperative Glasgow Coma Scale (GCS) score affected 6-month mortality. However, no variables were found to be correlated with 6-month mRS scores. Further multivariate analysis demonstrated that 6-month mortality in the endoscopic evacuation group was significantly lower than that in the MIC evacuation group (OR = 4.346, 95% CI 1.056 to 17.886). The 6-month mortality rate in the preoperative GCS 9–14 group was significantly lower than that in the GCS 3–8 group (OR = 7.328, 95% CI 1.723 to 31.170). Compared with MIC evacuation, endoscopic evacuation significantly decreased 6-month mortality in SCH patients. These preliminary results warrant further large, prospective, randomized studies.

New developments in anti-biofilm intervention towards effective management of orthopedic device related infections (ODRI’s) - Ping Li; Zhenwu Gao; Zhenwei Tan; Jun Xiao; Li Wei; Yirui Chen (Biofouling, 2021)

NC10 bacteria promoted methane oxidation coupled to chlorate reduction - Zi-Yan Li; Xin Li; Bin Tan; Pan-Long Lv; He-Ping Zhao (Biodegradation, 2020)

Groundwater resources survey of tongchuan city using the audio magnetotelluric method - Zhi-min Xu; Jing-tian Tang; Guang Li; Hui-Cui Xin; Zhang-jian Xu; Xin-ping Tan; Jin Li (Applied Geophysics, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Production, safety, health effects and applications of diacylglycerol functional oil in food systems: a review - Yee-Ying Lee; Teck-Kim Tang; Eng-Tong Phuah; Chin-Ping Tan; Yong Wang; Ying Li; Ling-Zhi Cheong; Oi-Ming Lai (Critical Reviews in Food Science and Nutrition, 2020)

Correction to: Deoxynivalenol-induced alterations in the redox status of HepG2 cells: identification of lipid hydroperoxides, the role of Nrf2-Keap1 signaling, and protective effects of zinc - Wageh Sobhy Darwish; Zhen Chen; Yonghan Li; Hui Tan; Hitoshi Chiba; Shu-Ping Hui (Mycotoxin Research, 2020)

RETRACTED ARTICLE: Deoxynivalenol-induced alterations in the redox status of HepG2 cells: identification of lipid hydroperoxides, the role of Nrf2-Keap1 signaling, and protective effects of zinc - Wageh Sobhy Darwish; Zhen Chen; Yonghan Li; Hui Tan; Hitoshi Chiba; Shu-Ping Hui (Mycotoxin Research, 2020)

Geodynamic processes of the continental deep subduction: Constraints from the fine crustal structure beneath the Pamir plateau - Wei Li; Yun Chen; Ping Tan; Xiaohui Yuan (Science China Earth Sciences, 2020)

Ultraviolet photolysis of metformin: mechanisms of environmental factors, identification of intermediates, and density functional theory calculations - Wenting Lin; Xiaohan Zhang; Ping Li; Yongzhen Tan; Yuan Ren (Environmental Science and Pollution Research, 2020)

Advances in Urban Meteorological Research in China - Shiguang Miao; Weimei Jiang; Ping Liang; Hongnian Liu; Xuemei Wang; Jianguo Tan; Ning Zhang; Ju Li; Wupeng Du; Lin Pei (Journal of Meteorological Research, 2020)

Three Chemosensory Proteins Involved in Chemoreception of Oedaleus asiaticus (Orthopera: Acridoidea) - Yuan-Tao Zhou; Ling Li; Xiao-Rong Zhou; Yao Tan; Bao-Ping Pang (Journal of Chemical Ecology, 2020)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

A new abietane diterpenoid glycoside from ajuga ovalifolia var. calantha - Fan Yang; Hong-Ping Chen; Xiao-Fei Shen; Hu-Lan Chen; Yin Chen; Li-Xia Wang; Hai Zhang; Wen-Ji Zhao; Mei Zhang; Yu-Zhu Tan (Natural Product Research, 2019)

Pharmacokinetic study of imrecoxib in patients with renal insufficiency - Qi Pei; Jin-lian Xie; Jie Huang; Wen-yu Liu; Xiao-yan Yang; Yan Wang; Wei Li; Hong-yi Tan; Hao Zhang; Guo-Ping Yang (European Journal of Clinical Pharmacology, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

Synthesis and biological evaluation of novel SIPI-7623 derivatives as farnesoid X receptor (FXR) antagonists - Si-Yun Nian; Guo-Ping Wang; Zheng-Li Jiang; Ying Xiao; Mo-Han Huang; Yi-Huan Zhou; Xiang-Duan Tan (Molecular Diversity, 2019)

Plot-scale spatiotemporal variations of CO2 concentration and flux across water–air interfaces at aquaculture shrimp ponds in a subtropical estuary - Yifei Zhang; Ping Yang; Hong Yang; Lishan Tan; Qianqian Guo; Guanghui Zhao; Ling Li; Yuchuan Gao; Chuan Tong (Environmental Science and Pollution Research, 2019)

Characterizing the Mass Elevation Effect across the Tibetan Plateau - Fang Han; Bai-ping Zhang; Fang Zhao; Li Wan; Jing Tan; Tian Liang (Journal of Mountain Science, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Antioxidative and antimicrobial activities of intertidal seaweeds and possible effects of abiotic factors on these bioactivities - Peihang Xu; Huaqiang Tan; Weiguang Jin; Yanfei Li; C. Santhoshkumar; Ping Li; Wenhua Liu (Journal of Oceanology and Limnology, 2018)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

The complete mitochondrial genome of Kele pig (Sus scrofa) using next-generation deep sequencing - Ya Tan; Kai-zhi Shi; Jing Wang; Chun-lin Du; Chun-ping Zhao; Xiong Zhang; Li Zhu; Yi-shun Shang (Conservation Genetics Resources, 2018)

Enhancement of the thermal and alkaline pH stability of Escherichia coli lysine decarboxylase for efficient cadaverine production - Fengyu Kou; Jing Zhao; Jiao Liu; Cunmin Sun; Yanmei Guo; Zijian Tan; Feng Cheng; Zhimin Li; Ping Zheng; Jibin Sun (Biotechnology Letters, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Detecting the Changes of Water Qualities and Fluorescent DOM in a Constructed Rapid Infiltration System - Ping-ping Gao; Yun-zhen Li; Xu-jing Guo; Tao Huang; Dong-hai Yuan; Xian-dong Tan (Wetlands, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Effects of Organic Acids and Sylvite on Phytoextraction of 241Am Contaminated Soil - Ping Wang; Liang Du; Zhaoyi Tan; Rongbo Su; Taowen Li (Bulletin of Environmental Contamination and Toxicology, 2017)

Evolution Mechanism and Rainfall Warning Criteria for Maijianwo Slope in Henan Province, China - Yi-heng Pan; Jian-ping Chen; Li-qing Wu; Wei Wang; Fu-lin Tan (Geotechnical and Geological Engineering, 2017)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

A Phytocystatin Gene from Malus prunifolia (Willd.) Borkh., MpCYS5, Confers Salt Stress Tolerance and Functions in Endoplasmic Reticulum Stress Response in Arabidopsis - Yanxiao Tan; Xiaoyu Wei; Ping Wang; Xun Sun; Mingjun Li; Fengwang Ma (Plant Molecular Biology Reporter, 2016)

Tissue-specific expression, developmentally and spatially regulated alternative splicing, and protein subcellular localization of OsLpa1 in rice - Hai-ping Lu; Wei-qin Pang; Wen-xu Li; Yuan-yuan Tan; Qing Wang; Hai-jun Zhao; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2016)

Flavobacterium buctense sp. nov., isolated from freshwater - Xiao-Min Feng; Xu Tan; Li Jia; Ping-Ping Long; Lu Han; Jie Lv (Archives of Microbiology, 2015)

Bacterial growth efficiency in a partly eutrophicated bay of South China Sea: Implication for anthropogenic impacts and potential hypoxia events - Xing-Yu Song; Hua-Xue Liu; Yu Zhong; Ye-Hui Tan; Geng Qin; Kai-Zhi Li; Ping-Ping Shen; Liang-Min Huang; You-Shao Wang (Ecotoxicology, 2015)

Neurology of the H1N1 pandemic in Singapore: a nationwide case series of children and adults - Asha Prerna; Jocelyn Y. X. Lim; Natalie W. H. Tan; Mas Suhaila Isa; Helen May-Lin Oh; Norazieda Yassin; Chian-Yong Low; Derrick W. S. Chan; Chia-Yin Chong; Yee-Sin Leo; Angela Li-Ping Chow; Paul Ananth Tambyah; et al. (Journal of NeuroVirology, 2015)

The dual role of autophagy under hypoxia-involvement of interaction between autophagy and apoptosis - Mengmeng Li; Jin Tan; Yuyang Miao; Ping Lei; Qiang Zhang (Apoptosis, 2015)

Over-expression of the MxIRT1 gene increases iron and zinc content in rice seeds - Song Tan; Rui Han; Peng Li; Guang Yang; Shuang Li; Peng Zhang; Wei-Bing Wang; Wei-Zhong Zhao; Li-Ping Yin (Transgenic Research, 2015)

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

A New Method of Change Point Detection Using Variable Fuzzy Sets Under Environmental Change - Jianzhu Li; Senming Tan; Zhaozhen Wei; Fulong Chen; Ping Feng (Water Resources Management, 2014)

Quantitatively analyze the impact of land use/land cover change on annual runoff decrease - Jianzhu Li; Senming Tan; Fulong Chen; Ping Feng (Natural Hazards, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Activation of BKCa Channels Mediates Hippocampal Neuronal Death After Reoxygenation and Reperfusion - Ming Chen; Hong-Yu Sun; Ping Hu; Chun-Fei Wang; Bo-Xing Li; Shu-Ji Li; Jian-Jun Li; Hui-Ying Tan; Tian-Ming Gao (Molecular Neurobiology, 2013)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

A novel Trichoderma species isolated from soil in Guizhou, T. guizhouense - Qi-Rui Li; Ping Tan; Yu-Lan Jiang; Kevin D. Hyde; Eric H. C. Mckenzie; Ali H. Bahkali; Ji-Chuan Kang; Yong Wang (Mycological Progress, 2013)

Lack of effect of continuous glycyrrhizin administration on the pharmacokinetics of the P-glycoprotein substrate talinolol in healthy volunteers - Miao Yan; Ping-Fei Fang; Huan-De Li; Ping Xu; Yi-Ping Liu; Feng Wang; Hua-Lin Cai; Qin-You Tan (European Journal of Clinical Pharmacology, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Sequence and phylogenetic analysis of H7N3 avian influenza viruses isolated from poultry in China in 2011 - Wu Hai-bo; Lu Ru-feng; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Xu Li-hua; Wu Nan-ping; Guo Chao-tan (Archives of Virology, 2012)

Genetic characterization of subtype H1 avian influenza viruses isolated from live poultry markets in Zhejiang Province, China, in 2011 - Hai-bo Wu; Chao-tan Guo; Ru-feng Lu; Li-hua Xu; En-kang Wo; Jin-biao You; Yi-ting Wang; Qiao-gang Wang; Nan-ping Wu (Virus Genes, 2012)

Characterization of a highly pathogenic H5N1 avian influenza virus isolated from ducks in Eastern China in 2011 - Wu Hai-bo; Guo Chao-tan; Lu Ru-feng; Xu Li-hua; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Wu Nan-ping (Archives of Virology, 2012)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Co-Variation Among Major Classes of LRR-Encoding Genes in Two Pairs of Plant Species - Jiao Wang; Shengjun Tan; Li Zhang; Ping Li; Dacheng Tian (Journal of Molecular Evolution, 2011)

A holistic approach to education programs in thalassemia for a multi-ethnic population: consideration of perspectives, attitudes, and perceived needs - Li Ping Wong; Elizabeth George; Jin-Ai Mary Anne Tan (Journal of Community Genetics, 2011)

Gα13 is closely related to hematopoiesis in zebrafish - Ding Ye; Qiwen Yang; Yang Li; Xinyun Huang; Jiarui Hu; Shiguang Qian; Zheng Tan; Ping Song (Molecular Biology Reports, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

High-mobility group box 1 exacerbates concanavalin A-induced hepatic injury in mice - Quan Gong; Hui Zhang; Jun-hua Li; Li-hua Duan; Shan Zhong; Xiao-ling Kong; Fang Zheng; Zheng Tan; Ping Xiong; Gang Chen; Min Fang; Fei-li Gong (Journal of Molecular Medicine, 2010)

Protective effect of selaginellin on glutamate-induced cytotoxicity and apoptosis in differentiated PC12 cells - Chen-Jing Wang; Chang-Ping Hu; Kang-Ping Xu; Qiong Yuan; Fu-Shuang Li; Hui Zou; Gui-Shan Tan; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Molecular alteration of Cav1.2 calcium channel in chronic myocardial infarction - Ping Liao; Guang Li; De Jie Yu; Tan Fong Yong; Jue Jin Wang; Jing Wang; Tuck Wah Soong (Pflügers Archiv - European Journal of Physiology, 2009)

Cloning and Characterization of Two Novel Crystal Protein Genes, cry54Aa1 and cry30Fa1, from Bacillus thuringiensis Strain BtMC28 - Furong Tan; Jun Zhu; Jie Tang; Xueming Tang; Shiquan Wang; Aiping Zheng; Ping Li (Current Microbiology, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Protective effects of daviditin A against endothelial damage induced by lysophosphatidylcholine - De-Jian Jiang; Jun-Lin Jiang; Gui-Shan Tan; Yan-Hua Du; Kang-Ping Xu; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Identification of quantitative trait loci (QTLs) for the characters of vascular bundles in peduncle related to indica-japonica differentiation in rice (Oryza sativa L.) - Zhi-Hong Zhang; Ping Li; Ling-Xia Wang; Chang-Jun Tan; Zhong-Li Hu; Ying-Guo Zhu; Li-Huang Zhu (Euphytica, 2002)